The Influence of Environmental Accounting on a Financial Performance - Yunita, Nur Afni; Yusra, Muhammad; Rais, Rany Gesta Putri; Edrayani, Dea (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2024)
This study aims to analyze the determination of environmental accounting with independent variables in the form of environmental performance, environmental costs, and the extent of CSR disclosure. The research sample consists of 31 companies in the basic and chemical industry subsectors for the period 2020-2022. The research method is quantitative, using panel data and purposive sampling to select research samples. The study showed that environmental cost variables affected financial performance, while environmental performance and CSR disclosure had no effect.